Language Function Of Slected Cosmetics Advertisement In Online Media - Ayu Anggraini Kambuna; Qammar-Un_Nisa Jatoi; Mohamed Jlassi (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This research aimed to find out the types of language function used in advertising cosmetics and describe how to use the language function of cosmetics advertisement in Online Media. Methodology: This study used a descriptive qualitative method. Data were collected from twelve selected cosmetics advertisements of brands such as Maybelline, Make Over, and Nyx Professional Makeup, accessed through Instagram, Facebook, YouTube, and official websites. The researcher used note-taking and documentation to classify data based on Halliday's language function theory. Main Findings: The findings revealed five types of language functions used in cosmetics advertisements: personal, representational, instrumental, imaginative, and interactional. The most dominant type was the personal function, followed by representational and instrumental. Heuristic and regulatory functions were not found. Advertisers used language functions to influence consumers by expressing emotion, conveying facts, and instructing behavior. Novelty/Originality of this study: This study offers new insight into the specific application of Halliday’s language function theory in Indonesian online cosmetics advertising. It emphasizes how language is strategically employed to build emotional engagement and persuade consumers in a digital marketing context.